Simple Two‐step, High Yield Protocol for Isolation and Amplification of Bacteriophages Against Methicillin‐resistant Staphylococcus Aureus (MRSA). Issue 3 (8th March 2022) - Khan, Atif; Joshi, Hiren
Abstract: Bacteriophages are bacteria‐targeting viruses that may prove useful as therapeutic agents against multidrug‐resistant bacterial strains. Though phage therapy is a century‐old concept, there is very limited progress on its therapeutic application due to the rapid expansion of antibiotics portfolios in the last few decades. However, the emergence of multidrug‐resistant organisms has brought our attention back to bacteriophages. The first step towards developing effective phage therapy against multidrug‐resistant bacteria is isolation, amplification, and purification of specific bacteriophages. There are many reported protocols for isolating host‐specific bacteriophages from the environment. However, most of them are complex, multistep, low‐yielding, resource‐intensive protocols, requiring elaborate laboratory setup. We have demonstrated a simple two‐step, high‐yielding protocol for isolating and amplifying bacteriophages against methicillin‐resistant Staphylococcus aureus (MRSA). We have shown that mixing various environmental samples (i.e., sample pooling) and phage amplification at two different temperatures significantly enhance the yield of MRSA phages. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of water sample filtrate for isolation of bacteriophages Basic Protocol 2 : Bacterial strain and culture conditions Basic Protocol 3 : Native bacteriophage count in water sample filtrate Basic Protocol 4 : Isolation and enrichment of MRSA‐specific bacteriophages Basic Protocol 5 : Quantification of bacteriophages by drop cast method Basic Protocol 6 : Effect of incubation temperature and heat shock on bacteriophage yield